The Effects of Curcumae Longae Radix, Curcuma phaeocaulis Radix and Their Processed Products on Epo/EpoR Pathway and CD62p - Zhimin Chen; Zhimin Chen; Wenbing Li; Wenbing Li; Liang Quan; Haiting Zhou; Yongfeng Zhao; Xi Zhang; Lin Hu; Changjiang Hu; Changjiang Hu (Frontiers Media S.A., 2018)
Background: Curcumae Radix (Yujin) has been widely used to treat Qi stagnation due to Liver depression (LDQS) in traditional Chinese medicine (TCM) for a long time and is good at dispelling melancholy by soothing liver to regulate qi and relieving pain by promoting blood circulation for removing blood stasis. Yujin stir-frying with vinegar can strengthen the effect of dispersing stagnated hepatoqi to stop pain by injecting medicine into the liver and stir-frying with wine can strengthen the effect of promoting blood circulation for removing blood stasis. Because the reason for the enhancement of clinical efficacy by processing is unclear, it is difficult to select and use processed products in the clinic.Aim/Hypothesis: In this study, from the point of view of the platelet function, we start to investigate the mechanism for promoting blood circulation, removing blood stasis, and enhancing clinical efficacy by processing.Methods: This study mainly takes Curcumae Longae Radix (HSYJ) and Curcuma phaeocaulis Radix (LSYJ) as the research subjects. They are genuine drugs in Sichuan Province, China. A high-performance liquid chromatography (HPLC) is used to analyze the main chemical constituents of Yujin and its processed products, and show the difference between the two species, with and without processing. A rat model of blood stasis induced by LDQS is established by giving the tail clamp stimulation, injecting epinephrine hydrochloride subcutaneously, and treating with an effective dose (0.9 g⋅kg-1) according to the conversion of human clinical dosage for 2 weeks. After the experiment, the serum levels of erythropoietin are measured by ELISA. Furthermore, RT-PCR and WB are used to detect EpoR mRNA and protein expression in the hepatic tissue. Flow cytometry is used to measure peripheral blood CD62p expression.Results: There is a great difference between the chemical compositions of the two species, the number of chromatographic peaks of Curcumae Longae Radix is more than that of Curcuma phaeocaulis Radix. Curcuminoids is the main component of HSYJ, while curcuminoids is almost free from LSYJ. Curcuminoids is almost insoluble in water. After stir-frying with vinegar or wine, it can increase the dissolution of curcuminoids in water. In rat models, the levels of Epo, EpoR, and CD62p are significantly increased. After intragastric administration of Yujin, indicators show varying degrees of callback. HSYJ is better than LSYJ, and the processed product by stir-frying with wine is better than other processed products.Conclusion: The results show that the mechanism of promoting blood circulation for removing blood stasis in Yujin may be able to inhibit the activation and aggregation of platelets by intervening the Epo/EpoR pathway and regulating CD62p down. Stir-frying with wine can enhance this effect.